2012
DOI: 10.22278/2318-2660.2009.v33.n2.a204
|View full text |Cite
|
Sign up to set email alerts
|

Detecção De Enteroparasitas Em Hortaliças Comercializadas Em Feiras Livres Do Município De Caruaru (Pe)

Abstract: O desenvolvimento de infecções parasitárias é causado pela precariedade sanitária e por maus hábitos de higiene. O objetivo deste estudo foi pesquisar a ocorrência de enteroparasitas de interesse para a saúde em hortaliças comercializadas na feira livre de Caruaru (PE). Foram colhidas 144 amostras de hortaliças, no período de outubro/2006 a junho/2007 e analisadas pelo método de sedimentação espontânea e método de Faust e cols. Observou-se que 15,27% das amostras estavam contaminadas por enteroparasitas: Alfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 12 publications
1
5
0
4
Order By: Relevance
“…An elevated number of intestinal parasites was detected in foliar vegetables commercialized in Aparecida de Goiânia, especially lettuce. The index of 70% positivity of lettuce samples is very high comparing with several others studies carried out in Brazil (Esteves and Figueirôa, 2009;Neres et al, 2011;Fernandes et al, 2015;Silva et al, 2015;Moura et al, 2016;Santos et al, 2017;Machado et al 2020); the nematode larvae were not included in statistics because they were not identified at the family, genus or species Occurrence of enteroparasites in foliar vegetables level, as they could be larvae of free-living non-parasitic nematodes. In addition, probable trematode eggs and Trypanoxyuris sp.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…An elevated number of intestinal parasites was detected in foliar vegetables commercialized in Aparecida de Goiânia, especially lettuce. The index of 70% positivity of lettuce samples is very high comparing with several others studies carried out in Brazil (Esteves and Figueirôa, 2009;Neres et al, 2011;Fernandes et al, 2015;Silva et al, 2015;Moura et al, 2016;Santos et al, 2017;Machado et al 2020); the nematode larvae were not included in statistics because they were not identified at the family, genus or species Occurrence of enteroparasites in foliar vegetables level, as they could be larvae of free-living non-parasitic nematodes. In addition, probable trematode eggs and Trypanoxyuris sp.…”
Section: Discussionmentioning
confidence: 77%
“…Despite the undeniable nutritional importance, raw or poorly washed vegetables contaminated with fecal residues or irrigated with water contaminated with parasitic forms have been reported as important vehicles for transmission of intestinal parasites to humans (Andrade et al, 2010;Fernandes et al, 2015). In Brazil, contamination of foliar vegetables is one of the main transmission routes of enteroparasites to humans (Soares and Cantos, 2005;Neres et al, 2011), and several studies have confirmed the presence of parasitic forms in vegetables commercialized in all regions of the country (Soares and Cantos, 2005;Esteves and Figueirôa, 2009;Neres et al, 2011;Gomes et al, 2014;Fernandes et al, 2015;Silva et al, 2015;Novacki et al, 2016;Santos et al, 2017;Maldonade et al, 2019;Machado et al, 2020;Rodrigues et al, 2020). However, in the State of Goiás there are still few reports on the occurrence of vegetables contaminated with parasitic forms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sua contaminação ocorre por diversas vias: cutânea quando a criança entra em contato com solo ou objeto contaminado ou oral por ingestão de ovos ou larvas (SANTOS et al 2010). Alimentos contaminados são um dos maiores agravos dessa parasitose, principalmente as que são ingeridas em saladas cruas, onde contem larvas e ovos desses helmintos, provenientes de águas contaminadas por materiais fecais de homens ou animais FIGUEIRÔA, 2012).…”
Section: Resultsunclassified
“…The washing solutions from each sample were filtered into a conical cup using a surgical gauze folded into four, resting for 24 hours. After this period, the materials were centrifuged at 9 000 rpm for 3 minutes, and the sediments obtained were transferred to test tubes (7,9).…”
Section: Sample Collectionmentioning
confidence: 99%